Quicklime as an alternative in the photodegradation of contaminants (2016)
Chemical oxidation is one of the many different methods of removing contaminants that has emerged recently, is an alternative method to traditional techniques. According to this research calcium peroxide is suitable choice for contaminant biodegradation in soil and ground water, but it happens at a very low speed. We hope that the method of synthesis of calcium peroxide in nano size by increased ratio of surface to volume can increase the speed of reaction and solve the problem. In the first synthesis of the material we obtained CaO instead of CaO2. Calcium oxide (CaO), commonly known as quicklime or burnt lime, is a widely used chemical compound in obtaining hypochlorite and to neutralize acidic soils. In this study we characterize the material by X-ray scanning electron microscopy, and ultraviolet-visible spectroscopy.